Impact of allergic bronchopulmonary aspergillosis overlap in chronic pulmonary aspergillosis - Shah,A (ERJ Open Research, 2026)
Background: Chronic pulmonary aspergillosis (CPA) is a destructive fungal infection caused by Aspergillus fumigatus, leading to significant morbidity in individuals with structural lung disease. Clinical and immunological overlap with allergic bronchopulmonary aspergillosis (ABPA) has been recognised, but its extent and prognostic relevance remain uncertain. This study assessed ABPA features in CPA and their relationship with immunological markers and long-term outcome.Methods: We conducted a retrospective cohort study including individuals with confirmed CPA at the Royal Brompton Hospital until December 2023. Diagnoses followed ERS/ESCMID and 2024 ISHAM criteria. Demographic, clinical, microbiological, and immunological data were analysed, and group comparisons performed using logistic regression and Cox proportional hazards models.Results: Among 166 individuals with CPA, 45 (27%) met ABPA diagnostic criteria. CPA–ABPA overlap was independently associated with asthma (OR-10.16) and pan-azole resistance (OR-19.37), and inversely with sarcoidosis (OR-0.22). Overall 5-year survival was 82% (84.6% in CPA alone vs 76.6% in overlap; p=0.44). Older age, lower BMI and albumin, elevated A. fumigatus-specific IgE and IgG were associated with higher mortality, while longitudinal increase in A. fumigatus-specific IgE was also linked to worse outcome. Low serum albumin independently predicted mortality (HR 0.72; p=0.001).Discussion: CPA–ABPA overlap represents a distinct clinical phenotype linked to airway disease, antifungal resistance, and Th2-driven inflammation. Nutritional status and immunological activity, particularly rising A. fumigatus-specific IgE, emerged as key prognostic markers, linking type 2 inflammation to disease progression. These findings highlight the need for phenotype-based risk stratification and exploration of targeted immunomodulatory strategies in CPA.